Urban sustainability indicators: Challenges and opportunities. (October 2018) - Verma, Pramit; Raghubanshi, A.S.
Graphical abstract: Highlights: Reviewed challenges of development and application of urban sustainability indicators. 2 categories of external and internal challenges identified with indicator framework. Discussed emerging and lesser researched areas in sustainability indicator. Propose indicator framework and three preliminary criteria for indicator selection. Abstract: Urbanization has become one of the most important issues which define the human relationship with the ecosystem. Measuring progress towards sustainable or unsustainable urban development requires quantification with the help of suitable sustainability indicators. There is a general ignorance about contextual meaning and understanding of the concept of sustainability which differs from country to country and economic strata of the society. Our review aims to reduce this challenge by identifying major issues faced in the development and implementation of sustainability indicators in an urban context and suggesting remedial recommendations. We have identified two broad categories of challenges according to their development and implementation phase respectively, and three preliminary criteria in the application of urban sustainability indicators.